Quality of Driving License Service at the Palu Police Station - Haprabu, Wiro; Daswati, Daswati; Ahmad, Ahsan; Salam, Rudi (Universitas Negeri Makassar, 2017)
Service is the process of fulfilling needs through other people's activities directly by becoming one of the indicators of government success towards the level of community satisfaction. This study aims to determine and describe the quality of driving permit services at the Palu Police Station. This study uses a descriptive qualitative research, in which this study attempts to reveal facts that are accurate and factually systematically about the service of a driver's license at the Palu Police station. This study uses the theory of Parasuraman, Zeithmal and Berry with indicators of direct evidence of direct evidence, reliability, responsiveness, assurance, attention. Data collection techniques are carried out through field research which includes observation, interviews and documentation. The technique of determining the informants in this study using purposive. Analysis of the data used is data reduction, data presentation and drawing conclusions. The results of this study indicate that, in general the officers making SIM in the Palu Sat Satas office are relatively fast and precise in providing information, and also in terms of the guarantee of the Palu police SIM management officers very maintaining public trust by not accepting bribery efforts in any form because rules for lawbreakers have been regulated in accordance with the article, although there are still a number of things that need to be addressed by the Palu Traffic Police Unit, such as the lack of instructions or in terms of direct evidence which says the buildings used are small.